MAKASSARESE AND BUGINESE LOCAL WISDOMS IN SCL-BASED WRITING CLASS (A CASE STUDY) - Ria Jubhari; Etty Bazergan; Karmila Mokoginta; Simon Sitoto; Besse Puspita Syarif; Ery Iswari (Soegijapranata Catholic University, 2016)
This descriptive-qualitative case study aims to (1) identify the values of Buginese/Makasaresse local wisdoms that shape the learning process of Hasanuddin University students attending the Writing2 (MBI2) subject in the even semester, 2014; (2) find out which of the local wisdoms that strongly shape the student-centred learning (SCL) process in the Writing II class. The study focused on students classroom interaction. Data were collected from classroom observations, questionnaires, interviews and teachers note on the learning process in classroom. This study found that what is thought as Buginese or Makassarese local wisdoms can both support and inhibit the SCL process in MBI2. Such local wisdoms include respect to older people and mutual help